Anodizing Characterization of Aluminum 1100 Composition of Sulfuric Acid - Oxalic Acid 16% With Aeration and Nonaeration at Different Time Intervals - Nurcahyo Nurcahyo; Rian Muhamad Rizky; Mangku Joyo Diningrat; Synbi Pasya Octaviarine Adihartanto; Tira Nur Khoirunisa; Tifa Paramitha (Journal of Green Science and Technology, 2025)
Aluminum is a type of metal that is widely used in the industrial and household fields. This study aims to analyze the effect of variations in sulfuric acid and oxalic acid concentrations, as well as aeration systems, on the surface characteristics of aluminum 1100 through the anodizing process. The anodizing process is one of the surface treatment processes that is carried out with the aim of improving or improving the properties of a metal, including resistance to wear, increasing hardness, and aiming to beautify the appearance itself. This anodizing test is with sulfuric acid-oxalic acid electrolyte solution, electrolyte concentration 16%, at room temperature with a current density of 3/dm2 in time intervals of 20 minutes and 30 minutes. The data obtained from the test results showed that the oxide layer was formed maximally in the aeration system with a concentration of 13.5+2.5 and a time interval of 30 minutes of 0.0411 gr. This shows that the addition of oxalic acid and oxygen can accelerate the formation of the oxide layer. At electrolyte concentrations of 16+0, 15.5+0.5, 15+1, 14.5+1.5 and 14+2, there was an increase in the difference in oxide mass by 0.0337 gr, 0.0335 gr, 0.0366 gr, 0.0390 and 0.0411 gr.